<h3>
Answer: G) -2</h3>
=======================================================
Explanation:
I'm assuming you meant to say (a+y)^2 + 2y
Replace each copy of 'a' with 5. Replace each copy of 'y' with -3. Use PEMDAS to simplify.
(a+y)^2 + 2y
(5 + (-3))^2 + 2(-3)
(5-3)^2 + 2(-3)
(2)^2 + 2(-3)
4 + 2(-3)
4 - 6
-2
So (a+y)^2 + 2y = -2 when a = 5 and y = -3.
Answer:
D,1
Step-by-step explanation:
In the attached file
It’s True because of 5 square is equal to 25
Than (-5) square is also get the same value as 5^2